2019
DOI: 10.1097/dcr.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Consecutive Fecal Calprotectin Levels in the Perioperative Period and Its Predictive Capacity for Early Endoscopic Recurrence in Crohn’s Disease

Abstract: BACKGROUND: The perioperative behavior of fecal calprotectin and whether it predicts early postoperative endoscopic recurrence of Crohn’s disease are unknown. OBJECTIVE: We aimed to compare the perioperative profiles of fecal calprotectin between patients with Crohn’s disease and patients without Crohn’s disease undergoing intestinal resection and to identify the association between consecutive fecal calprotectin levels and endoscopic recurrence 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…3 Our previous study showed that postoperative Fc could predict endoscopic recurrence at 3 months after surgery. 9 In the present study, we also found Fc >150 ug/g on postoperative day 14 could predict anastomotic scattered ulcers. These indicate that Fc could be one useful tool to screen out patients at high risk of postoperative recurrence 1 month after surgery.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…3 Our previous study showed that postoperative Fc could predict endoscopic recurrence at 3 months after surgery. 9 In the present study, we also found Fc >150 ug/g on postoperative day 14 could predict anastomotic scattered ulcers. These indicate that Fc could be one useful tool to screen out patients at high risk of postoperative recurrence 1 month after surgery.…”
Section: Discussionsupporting
confidence: 73%
“…Histologic recurrence of CD can occur as early as 1 week after surgery. 8 In our previous study, 9 more than 20% of patients suffered endoscopic recurrence at 3 months after surgery. It is not clear whether performing the first endoscopic evaluation at 1 month after surgery is necessary and useful for treatment adjustment.…”
mentioning
confidence: 85%
“…Consecutive elevated FC measurements in them can predict disease relapse in the upcoming 3 months with high sensitivity and specificity [5,6), thus serving as a tool to assess treatment efficacy. In addition, consecutive monitoring of FC perioperatively may be predictive of early postoperative endoscopic recurrence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Calprotectin is released by granulocyte activation and elevated level of fecal calprotectin (FC) is found in the GI tract inflammation that closely related to inflammatory bowel disease (IBD) activity . Increasing evidence indicates that FC can be used as a noninvasive marker for intestinal/colonic inflammation that helps clinicians distinguish organic inflammatory bowel disease (IBD) from functional irritable bowel syndrome (IBS) . Markers of systemic inflammation, such as C‐reactive protein (CRP) and white blood cells count, have low specificity and sensitivity for IBD, while the gold standard of ileo‐colonoscopy is invasive and expensive .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Increasing evidence indicates that FC can be used as a noninvasive marker for intestinal/colonic inflammation that helps clinicians distinguish organic inflammatory bowel disease (IBD) from functional irritable bowel syndrome (IBS). [4][5][6] Markers of systemic inflammation, such as C-reactive protein (CRP) and white blood cells count, have low specificity and sensitivity for IBD, while the gold standard of ileo-colonoscopy is invasive and expensive. 3 Thus, noninvasive method for monitoring disease activity is preferable.…”
Section: Introductionmentioning
confidence: 99%